Treatment with High Dose Rifampicin in Tuberculous Meningitis: A Case Report - Ketaren, Retno J; Goenawan, Vonny; Simca, Jennifer (Fakultas Kedokteran Universitas Pelita Harapan, 2019)
Introduction : Tuberculous meningitis continues to be associated with considerable mortality and morbidity.A randomized comparison of higher-dose intravenous rifampicin (approximately 13 mg/kg per day) versus a standard oral dose in adults with tuberculous meningitis showed that mortality among patients who received higher intravenous dose was 50% lower than those who received the standard dose.1 While there are other contradictory results regarding the use of high-dose rifampicin in patients with tuberculous meningitis.Method : We hereby report a case of a 20-year-old female patient presented with a history of fever, palpable neck lymph nodes and headache since 1 month before admission. Neurological examination revealed nuchal rigidity without other neurological deficits. Head MRI with contrast showed meningitis with tuberculoma in the right parietal lobe +/- 0.4 cm and neck ultrasonography showed multiple lymphadenopathy with 1 cm in diameter. Cerebrospinal fluid examination revealed tuberculous meningitis. The patient had been treated with rifampicin 450 mg, other tuberculosis regiments, levofloxacin, and dexamethasone. After one week of treatment, the patient developed generalized seizure and deterioration of consciousness. Imaging re-evaluation showed multiple acute infarction in the cortical and subcortical left frontal lobe, bilateral insula, bilateral temporal lobe, right parietal lobe to the corpus callosum, more prominent leptomeningeal contrast, and communicating hydrocephalus. Ventriculoperitoneal shunt was done. The patient was then treated with a higher dose of Rifampicin (15 mg/kg 900 mg) and showed improvement after 2 weeks of treatment without any abnormal laboratory findings.Conclusion : The usage of high dose rifampicin is still controversial. From this case we can conclude that by giving high dose rifampicin, the patient has a better outcome without any significant side effects. Thus, we support the hypothesis of using high-dose rifampicin in patients with tuberculous meningitis that does not respond to the standard treatment.